Effectiveness of Endorphin Massage in Reducing Labor Pain During the Active Phase of the First Stage of Labor at Independent Midwifery Practice (PMB) E, Mustika Jaya, Bekasi (2025–2026) - Emilia Emilia (Public Health Journal, 2026)
Excessive and prolonged labor pain can lead to anxiety, psychological distress, labor complications, and even maternal and neonatal mortality. Therefore, it is necessary to manage labor pain using non-pharmacological methods, such as endorphin massage. This study aims to determine the effectiveness of endorphin massage in reducing labor pain during the active phase of the first stage of labor among women giving birth at PMB E Mustika Jaya, Bekasi.This study employed a quasi-experimental method with a one-group pre-test/post-test design, involving a sample of 30 women in the first stage of labor. The Numeric Rating Scale (NRS) was used to measure pain intensity before and after endorphin massage. Data analysis was conducted using the non-parametric Wilcoxon Signed-Rank test.The analysis yielded a p-value of